Evaluation for systemic mastocytosis in adults with cutaneous mastocytosis - Laosakul, Kulwadee; Chiewchanvit, Siri; Tovanabutra, Napatra; Mahanupab, Pongsak; Chuamanochan, Mati (Biomedical Sciences and Clinical Medicine, 2017)
In adults with cutaneous mastocytosis there is a high probability of systemic involvement, which can lead to anaphylaxis. Consequently, when cutaneous mastocytosis is diagnosed in adults, it is important to also check for systemic involvement. A 30-year-old Singaporean man presented with generalized asymptomatic monomorphic brownish macules and papules. The lesions were aggravated by consumption of alcohol. Light microscopic study and immunohistochemistry staining results were consistent with cutaneous monomorphic maculopapular mastocytosis. Symptomatic treatment with antihistamine was prescribed and he was advised to avoid alcohol. The patient indicated he would seek further evaluation in Singapore